Research of Factors Influencing the Subchannel Allocation to Subscriber Stations in WiMAX - Лемешко, О. В.; Hailan Ahmad; Al-Janabi Haider Dheyaa Kamil; Hojayev Oraz (My University, 2015)
Model of subchannel allocation in WiMAX network based on solution the optimization problem associated with maximizing the lower level allocated bandwidth for each subscriber station according to its quality of service requirements for access rate was investigated. Research of proposed model confirmed the adequacy and effectiveness of solution in terms of providing different types of service level (with and without guaranties) to subscriber stations. Results showed that the number of subchannels allocated to subscriber stations with a deficit of network resource adaptive reduction of provided level of quality of service performed dependently on the type of possible guaranties and requirements regarding the access rate.
Keywords: Телекоммуникации; WiMAX; OFDMA; subchannel; allocation; subscriber station